Root canal microbiota as an augmented reservoir of antimicrobial resistance genes in type 2 diabetes mellitus patients (Journal of Applied Oral Science, 2023)
Antimicrobial resistance is a global public health problem. Root canal microbiota associated with apical periodontitis represents a well-known reservoir of antimicrobial resistance genes (ARGs). However, the effect of type 2 diabetes mellitus (T2DM) in this reservoir is unknown. This study aimed to establish if root canal microbiota associated with apical periodontitis in T2DM patients is an augmented reservoir by identifying the prevalence of nine common ARGs and comparing it with the prevalence in nondiabetic patients. Methodology: This cross-sectional study included two groups: A T2DM group conformed of 20 patients with at least ten years of living with T2DM and a control group of 30 nondiabetic participants. Premolar or molar teeth with pulp necrosis and apical periodontitis were included. A sample was collected from each root canal before endodontic treatment. DNA was extracted, and ARGs were identified by polymerase chain reaction. Results: tetW and tetM genes were the most frequent (93.3 and 91.6%, respectively), while ermA was the least frequent (8.3%) in the total population. The distribution of the ARGs was similar in both groups, but a significant difference (p<0.005) was present in ermB, ermC, cfxA, and tetQ genes, being more frequent in the T2DM group. A total of eighty percent of the T2DM patients presented a minimum of four ARGs, while 76.6% of the control group presented a maximum of three. Conclusions: Root canal microbiota associated with apical periodontitis in T2DM patients carries more ARGs. Therefore, this pathological niche could be considered an augmented reservoir.